Establishment and characterization of a human juvenile bone marrow-derived mesenchymal stem/stromal cell line under advanced culture conditions for osteogenic differentiation - Moldaschl, Julia; Danilchenko, Sofia; Sagar, Isita; Brandt, Vivian-Pascal; Holland, Heidrun; Handschuh, Stephan; Glösmann, Martin; Toegel, Stefan; May, Tobias; Egger, Dominik; Kasper, Cornelia (Frontiers in Bioengineering and Biotechnology, 2026)
Human mesenchymal stem/stromal cells (MSC) from juvenile donors (juvMSC) are crucial for studying bone development and for modeling pediatric skeletal diseases. However, the limited availability of these cells and the lack of physiologically relevant in vitro models hinder preclinical research. To address these issues, we established and characterized a new human bone marrow-derived MSC line under advanced culture conditions. Primary MSC from a 12-year-old donor in good health were immortalized via lentiviral transduction using a library of expansion genes. The resulting clone, C15 juvMSC, retained key features of MSC, including typical morphology, high proliferation rate, expression of stemness surface markers, and trilineage differentiation in a 3D format. Spectral karyotyping confirmed genomic stability without chromosomal aberrations. In 3D spheroid cultures, the C15 juvMSC demonstrated strong osteogenic potential, as evidenced by mineralization and alkaline phosphatase (ALP) activity. However, they exhibited a distinct differentiation pattern compared to primary cells. Overall, the C15 juvMSC line exhibits stable, scalable, and physiologically relevant characteristics, making it a valuable model for studying osteogenesis and for in vitro research on pediatric bone disorders.